An Economic Analysis of Sand Goby Cage Culture in Thailand - Pochanapan, Chatchai (1987)
Sand Goby is an important species of inland cage culture. Sand Goby has the highest average price among all the fishes. Productivity of Sand Goby cage culture seems low compared to its potential. The main focus of this study is to find ways to increase productivity of Sand Goby cage culture which could reduce per unit cost of production, leading to increased profit. A restricted profit function is employed to estimate jointly the profit and factor demand functions using farm-level data. The relative economic efficiency (included technical and price efficiency) between small and large farms, between farmers with experience more than mean and farmers with experience less than or equal to the mean were studies. The effect of province on economic efficiency is also analysed. The Cobb-Douglas normalized restricted profit function is specified as a function of three normalized variables (labour, fingerling and feeds), two quantities of fixed inputs (capital and volume of cages) and three durrmy variables (large farms, farmers with experience more than the mean and farms in Lopburi province). The results indicate that Sand Goby farmers maximize short term prof its and respond to price changes efficiently. There is constant returns to scale in the use of inputs. Farmers with experience more than the mean have higher economic efficiency compared to the farmers with experience less than the mean. Farmers in Lopburi also has higher economic efficiency compared to farmers in Phranakhon Sriayutthaya. There is no significant difference in economic efficiency between large and small farms. The supply elasticity of Sand Goby with respect to its own price is the highest compared to other supply elasticities. It is recommended that Sand Goby cage culture be encouraged further in Lopburi province. Consolidation of small farms into larger-sized units would not be desirable. Furthermore, since the price of Sand Goby is the most effective in terms of affecting changes in output supply and factor demand, the price of Sand Goby would be the most powerful policy instrument available.